4(8t-7)-111=3(5t-7)+2(9t-11)
Answers
Answered by
1
Step-by-step explanation:
I HOPE ITS HELP YOU PLEASE MARK ME AS BRAIN LIST
Attachments:
![](https://hi-static.z-dn.net/files/d0c/c690f4fe8c77dc61e21289f69af61cb9.jpg)
Answered by
0
Answer:
-96
Step-by-step explanation:
32t-28-111=15t-21+18t-22. 32t-28-111=33t-43. 32t-139-33t+43=0. -t-96=0. t+96=0. then we get t=-96
Similar questions
Business Studies,
1 month ago
India Languages,
3 months ago
English,
11 months ago
English,
11 months ago
Math,
11 months ago